LEGAL STUDY OF VISUM ET REPERTUM IN THE STAGE OF THE INVESTIGATION IN DISCLOSING THE CRIME FOLLOW-UP - I Gst A.A Sintiana Dewi (Ganesha Civic Education Journal, 2020)
This study aims to determine and analyze the function of Visum Et Repertum in investigations in revealing rape crime. This type of research is a type of normative juridical research, then the approach in this research is the statutory approach (statute approach), case approach (case approach. As a normative juridical study, this research uses legal materials, consisting of primary legal material, secondary legal material, and tertiary legal material The technique of gathering legal materials used by the study of documents and literature studies The results of the study show (1) the role of the Visum Et Repertum in the examination of a rape crime in addition to assisting investigators in uncovering criminal acts but also plays an important role in the hearing at the hearing, then the effort of the investigator requesting the making of a visum et repertum from the initial stage of the examination of the case is important and must be done. two tools, ma'am The quality required for a judge in deciding a case as this is determined in Article 6 paragraph (2) of Law No. 14 of 1970 concerning the Principal Provisions of Judicial Power, and (2 In Criminal Cases, Visum Et Repertum is located as a valid evidence in Article 184 paragraph (1) of the Criminal Procedure Code. So in this case, investigators should include evidence such as Visum Et Repertum as evidence to strengthen and discover the truth of the occurrence of rape.